Fundamentals Studies Of Electro-Silver Plating Process. - Siah, C.H.; Aziz, N; Samad, Z; Noordin, N.; Idris, M. N.; Miskam, M.A. (2004)

(untitled)
The growth of electronic industry as a whole, and the demand to support the expansion of its underlying infrastructure will continue to drive the improvements in electroplating process. In order to improve existing electroplating process, the study of fundamentals aspects for electroplating process has become important.